OPTIMALISASI KINERJA ALAT PENGHASIL ASAP CAIR DARI BAHAN BAKU LIMBAH PERTANIAN - Sinar Abrina Anggraini; Tiya Nurhazisa (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
Currently the rottenable food material needs for preservation technology that was safe for people's health. Recently, liquid smoke technology which is used as an alternative material of food preservatives is from any agricultural waste. Liquid smoke beginning to develop by researchers, to get the higher quality in order to become safe for consumption by the public and not contains carcinogenic substance. The purpose of this study was to determine the performance of liquid smoke tools, the quantity and quality of liquid smoke. In this research, the material used was corn cob and coconut shell using the main tool of pyrolysis reactor, with the optimum operating conditions and then analyzed using GC/MS and LC/MS. The result showed that the yield of liquid smoke coconut shell without drying and through drying was 36% and 28.8%, while from the corn cob was 61.2% and 30.4%. Charcoal of coconut shell 33% and 50% while from the corn cob was 16.7% and 33.3%. The number of missing components from coconut shell is 31% and 21.2% while from the corn cob was 22.1% and 36.3%%. Performance of liquid smoke tools from coconut shell is 4.37 g/(hour.m) and 5.59 g/(hour.m) while from corncobs is 7.42 g/(hour.m) and 7.37 g/(hour.m). The phenol quality of the resulting liquid smoke from coconut shell and corncob was 3.04% and 1.38%. Acidity quality was 7.3% and 1.3%. The value of pH was 1.41 and 2.47.